2023
DOI: 10.1002/epi4.12701
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based structural and functional MRI outcomes in the rat brain after soman (GD) exposure‐induced status epilepticus

Abstract: Objective: Exposure to the nerve agent, soman (GD), induces status epilepticus (SE), epileptogenesis, and even death. Although rodent models studying the pathophysiological mechanisms show females to be more reactive to soman, no tangible sex differences in brains postexposure have been reported. In this study, we used multimodal imaging using MRI in adult rats to determine potential sexbased biomarkers of soman effects.Methods: Male and female Sprague Dawley rats were challenged with 1.2 × LD 50 soman followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…SE-induced long-term effects on the brain structure and functions in experimental models of epilepsy are well known [ 21 , 36 , 44 ]. Soman-induced long-term effects, especially the changes in the hippocampus and amygdala, have been demonstrated in rat models [ 36 , 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SE-induced long-term effects on the brain structure and functions in experimental models of epilepsy are well known [ 21 , 36 , 44 ]. Soman-induced long-term effects, especially the changes in the hippocampus and amygdala, have been demonstrated in rat models [ 36 , 45 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…SE-induced long-term effects on the brain structure and functions in experimental models of epilepsy are well known [21,33,41]. Soman-induced long-term effects, especially the changes in the hippocampus and amygdala, have been demonstrated in rat models [33,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…T1- or T2-weighted MRI intensities have been used to assess brain pathology in the GD model ( Bhagat et al, 2001 , 2005 ; Gullapalli et al, 2010 ; Reddy et al, 2020 ; Gage et al, 2023 ). Although no difference in T1 and T2 intensity was observed at the ROI levels between groups in this study, the voxel-wise analysis revealed significant T1 decreases and T2 increases after GD exposure, which was consistent with previous reports ( Gullapalli et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although structural MRI changes have been well characterized in OPNA toxicity ( Bhagat et al, 2001 , 2005 ; Gullapalli et al, 2010 ; Reddy et al, 2020 ), the use of fMRI to assess functional network connectivity and disease modification has not been investigated. We recently reported the differential findings in structural and functional MRI of brains between male and female rats in the GD-induced epilepsy model ( Gage et al, 2023 ). The current study aims to examine the potential disease-modifying effects of an iNOS inhibitor, 1400W, against GD intoxication.…”
Section: Introductionmentioning
confidence: 99%